LEVANTAMENTO DE RISCOS AMBIENTAIS NA ATIVIDADE DE CONSTRUÇÃO E MONTAGEM DE SISTEMAS ELÉTRICOS NA EXPLORAÇÃO DE PETRÓLEO ON SHORE - Jeronimo, Carlos Enrique; Duarte, Alcimar; Paiva, Enver (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2012)
http://dx.doi.org/10.5902/223611705919 This work presents a survey of companies that provide construction services and installation inelectrical systems in the area of drilling and oil exploration. The study was conducted in the regionof Mossoró in the state of Rio Grande do Norte. The objective was to identify and analyze thephysical agents to which workers are exposed, proposing mitigation measures to reduce theharmful consequences, as well as presenting the good practices of companies with investmentsand improvements in the productive process. The study is the development of the risk matrix,using the tool of the preliminary risk analysis (PRA) and subsequent analysis of the regulatoryinstructions and original methods of operation, developed by the workers themselves. It alsodescribes the phases of the tasks and risks associated physical and its correlation withenvironmental factors, constituting an important element for the development of a system ofprevention of occupational diseases for all companies operating in the following distribution ofelectricity for petroleum companies.